2006
DOI: 10.2166/wst.2006.474
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Cryptosporidium infection and drinking water source: a systematic review and meta-analyses

Abstract: Cryptosporidium is a well-known cause of diarrhoea in humans. Little is known about risk factors associated with endemic cryptosporidiosis, which constitutes the majority of cases. We carried out meta-analyses to verify if drinking water is also associated with endemic infection and to assess the magnitude of the associations. The global meta-analysis suggests that there is an increased risk of Cryptosporidium infection among unsafe water users (OR 1.40 [1.15, 1.72]). Studies were stratified, according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…51 In a meta-analysis study, drinking boiled water was associated with a 38% reduction in the risk of endemic cryptosporidiosis. 52 In this study too, children belonging to families who always boiled their drinking water had a significantly lower risk of multiple cryptosporidial infections and cryptosporidial diarrhea than those drinking unboiled water, although no protection against cryptosporidiosis overall or asymptomatic infections was observed. Additionally, providing a protected drinking water source (bottled drinking water) did not prevent or delay cryptosporidial infections (both symptomatic and asymptomatic) in children in the same community.…”
Section: Discussionmentioning
confidence: 54%
“…51 In a meta-analysis study, drinking boiled water was associated with a 38% reduction in the risk of endemic cryptosporidiosis. 52 In this study too, children belonging to families who always boiled their drinking water had a significantly lower risk of multiple cryptosporidial infections and cryptosporidial diarrhea than those drinking unboiled water, although no protection against cryptosporidiosis overall or asymptomatic infections was observed. Additionally, providing a protected drinking water source (bottled drinking water) did not prevent or delay cryptosporidial infections (both symptomatic and asymptomatic) in children in the same community.…”
Section: Discussionmentioning
confidence: 54%
“…A SR and MA of the impacts of weather on surface waters indicated that contamination with Cryptosporidium and Giardia was 2.61 and 2.87 higher during and after heavy rainfall [139]. A SR was used to examine the risks of endemic cryptosporidiosis, and found increased risk associated with the unsafe use of water [140]. This makes the need for risk assessment necessary.…”
Section: Protozoamentioning
confidence: 99%
“…Various drinking water choices affect access to quality of water and then induce different risk for health [3,4]. Studies have suggested drinking water choices may vary by gender, age, education, economic status, risk perception and personal health belief [5-11].…”
Section: Introductionmentioning
confidence: 99%